B-N-Acetilhexosaminidase involvment in a-conglutin mobilization in Lupinus albus - Santos, Cláudia N. (2013)
Glycosylation is an important post-translational modification involved in the modulation of a wide variety of cellular processes. Because glycosydases are central, the aim of this study was to investigate the glycosyl activity present in the cotyledons of the seeds of an important crop legume, Lupinus albus, as well as potential natural substrates of the detected enzymes. The glycosyl activity detected in the cotyledons beginning at seed imbibition and continuing until 9 days after, was due to a -N-acetylhexosaminidase ( -NAHase), which was molecularly and biochemically characterized after purification. Two isoenzymes with molecular masses of 64 and 61 kDa were detected, each having five isoenzymes with pIs 5.3–5.6. The 64 and 61 kDa isoenzymes had the same protein core showing different degrees of glycosylation. The N-terminal sequence of the enzyme protein core was determined [VDSEDLI(EN)AFKIYVEDDNEHLQGSVD] and to our knowledge, is the first reported protein sequence from a plant -NAHase. L. albus -NAHase had Km values of 2.59 mM and 2.94 mM and V values of 18.40 M min−1 and 2.73 M min−1, for pNP–GlcNAc and pNP–GalNAc, an optimum pH of 5.0 and 4.0 and temperature of 50 ◦C and 60 ◦C were detected toward pNP–GlcNAc and pNP–GalNAc. In the presence of AgNO3, CoCl2, CuSO4, FeCl3, CdCl2 and ZnCl2 the enzymatic activity decreased more than 50%, and when in the presence of sugars, an activity reduction of no more than 25% was observed. A physiological role for -NAHase in L. albus storage protein mobilization was investigated. -NAHase has already been implicated in several biological processes, namely in glycoprotein processing during seed germination and seedling growth. However, the natural substrates used by this enzyme are not yet completely clarified. By gathering in vivo and in vitro data for -NAHase activity together with globulin degradation, we suggest that L. albus -NAHase is involved in the mobilization of storage protein degradation, with - conglutin being a potential natural substrate for this enzyme